FINANCIAL STABILITY OF THE UKRAINE NATIONAL SYSTEM OF PENSION INSURANCE - A. Khemii (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The system of pension insurance is a combination of created by the state legal, economic and organizational institutions and norms, providing financial support to citizens in the form of pensions. In the article analyzing the demographic situation and the condition of pension payments in the country today. In the terms of economic and social reforms, the level of financial stability the pension system is low. Therefore important is the analysis and exploring new methods to ensure financial stability of the Ukraine national system of pension insurance. The main institution of the national pension insurance is the National Pension Fund of Ukraine.